Roald Amundsen - fortellinger om en polarhelt - Aarekol, Lena (Nordlit, 2012)
2011 is the Nansen-Amundsen Year in Norway. This year celebrate two anniversaries with great significance for Norway. It is 150 years since the birth of Fritdjof Nansen and 100 years since Roald Amundsen, accompanied by four of his men, arrived as the first at the South Pole. During this year several new exhibitions has been made and displayed in different museums in Norway. The article surveys the role of today's museums has in forming the narratives about the Norwegian polar history, the polar heroes and Roald Amundsen especially. An examination of a so called traditional Polar exhibition shows that their main focus on artifacts and theirlack of contextualization, gives the exhibition an aura of authenticity. While new exhibitions are characterized by emphasis on contextualization, critical questions and giving different groups a voice. It is argued that the museums both contributes to conserve the prevailing concepts and representations, but also contributes to give new understandings and perspectives of Roald Amundsen and the Norwegian Polar history. It is important to understand how the museums exhibitions are contributing to the collective memory.
Keywords: Museer; museologi; formidling; polarhistorie; Roald Amundsen; urbefolkning; inuitt; polarhelter; fotografi.